Obstetrical Complication Associated with Advanced Maternal Age – Experience of Damascus University Maternity Hospital - السقا كنعان; أبو طوق عزام; أحمد محمد محمد (Latakia University Journal -Medical Sciences Series, 2020)
This research aims to study the complications associated with pregnancy and childbirth in women ≥ 40 years of age and compare them with those in women aged 20-40 years. Where it was found that there is a statistically significant correlation between advanced maternal age and each of: Pre-eclampsia, premature birth, caesarean section, newborn weight, and the presence of a story of spontaneous projections. This research also showed an unimportant increase in the incidence of early placental abruption in the advanced maternal age group, and no significance was recorded for the development of gestational diabetes in the same previous group.